Brand Loyalty of Baby Diaper Products - Shrestha, Sajeeb Kumar (Management Dynamics, 2018)
This study tries to measure the factors influencing brand loyalty of baby diapers in Kathmandu City. Primary cross section data were collected using structured questionnaires. 200 working mothers were chosen as sample of the study. Reliability analysis, descriptive statistics and regression analysis was done to filter the questions, to summarize the data and to test the hypotheses. This research confirmed convenience, product quality, design, brand experience and brand image factors are important factors for brand loyalty of baby diaper products. Price has no support for brand loyalty.